Primary pulmonary mucosa-associated lymphoid tissue lymphoma with extensive lung involvement and negative autoimmune and inflammatory background: A case report and literature review - Abdulrahman I. Alabdulgader; Arwa A. Nabhan; Arwa M. Althubaity; Abir H. Alsaid; Hind S. Alsaif; Hossain A. Abualola; Mohammed A. Al-Mulhim; Ahmed A. Alsayyah; Mohammed I. Aldarweesh (Journal of Family and Community Medicine, 2024)
Primary pulmonary mucosa-associated lymphoid tissue (MALT) lymphoma is a very rare presentation of MALT lymphoma. The presence of a completely negative autoimmune and inflammatory background makes it a real challenge and very rare presentation (probably the second reported case in the literature). We report a case of primary pulmonary MALT lymphoma with negative autoimmune background, demonstrating as multifocal bulky variceal masses causing significant clinical symptoms.